دراسة في النواحي الادارية والاجتماعية والاقتصادية في العهد العثماني المتأخر 1848 م 1915 م - سمير (مجلة كلية التربية, 2020)
Zubair spend (AL Kahlaa) Study in the Administrative Social and Economic aspects (1848-1915). Zubair spend located (AL Kahlaa) in the South-West of the City of Amara, A distance of 30Km on the right bank of the river AL Kahlaa branching from the left side of the Tigirs river at the city of Amara was the first orderd to the village spread out houses around the castle built by Sheikh Faisal bin Khalifa,Chairman of the tribe Albou Mohammed in 1848 in the center of the Territory Msheechth after the release of his tribe from the influence of Bani Lam it was called MsieidnVillage name and when the foundation spend architecture 1861, became Msieidn land in 1869 linked to the banner of Architecture center in 1881 it was promoted from hand to Zubair associated several agricultural districts characterized the fertility o its soil and frequently where cattle Buffalo then launched AL Kahlaa name on Zubair.